Solvent Characterization of Lycopene Extraction in Tomato Fruits as Sensitizer Candidates in Dye-Sensitized Solar Cell (DSSC) - Devi Ayu Septiani; Agus Abhi Purwoko; Aliefman Hakim (Jurnal Biologi Tropis, 2022)
This study is an experimental study aimed at clarifying the characteristics of the solvent in the extraction of lycopene in tomato (Solanum lycopersicum) as a candidate photosensitizer for dye-sensitized solar cells (DSSC). The performance of DSSC  depends on the type of dye commonly used as a sensitizer. Tomatoes contain an lycopene. Yields of lycopene extract in tomatoes were characterized by FTIR and UV-Vis spectrophotometers. The extraction methods used in this study are the maceration method and liquid-liquid extraction. The procedure of this study was carried out in two main stages,  the extraction stage and the characterization stage. The first step was the extraction of lycopene from tomatoes using the maceration and liquid-liquid extraction methods. The maceration process compared the use of acetone and ethyl acetate as solvents. This extraction step produced  6.514 g (acetone) and 5.6702 g (ethyl acetate) lycopene extracts. The second step is to identify the functional groups of the compound formed using an FTIR spectrophotometer and use a UV-Vis spectrophotometer to determine the absorbance and maximum wavelength value of the lycopene and  M-lycopene complex. The results of the FTIR spectrophotometer test showed that using acetone as the solvent produced wavenumbers similar to lycopene compared to ethyl acetate.  UV-Vis spectrophotometer test results show the maximum wavelengths of the lycopene extract using acetone as the solvent were 447 nm, and 294 nm when ethyl acetate was used as the solvent. The Eg results revealed that the Eg values ​​for the acetone and ethyl acetate extracts were 4.52 eV and 2.68 eV. Based on the results of property analysis of the two solvents used, acetone was more suitable than ethyl acetate for the extraction of tomato lycopene used as a DSSC sensitizer.